Smart materials and intelligent systems : selected, peer reviewed papers from the 2011 international conference on smart materials and intelligent systems (SMIS 2011), December 23-25, 2011, Chongqing, China - Zhong, Shaobo; Qu, Xilong (Advanced materials research ;, 2012)
The aim of this special volume is to facilitate the exchange of information on the best practices for multifunctional materials, active materials, enabling technologies and integrated system design, intelligent systems and applications, etc. It provided an opportunity for engineers and scientists in academia, industry and government to address the most innovative research and developments, including technical challenges, social and economic issues, and to discuss their ideas and results in all aspects of Smart Materials and Intelligent Systems. Review from Book News Inc.: This collection of ar.